Rectus Muscle Resection for Vertical Strabismus in Thyroid Eye Disease. (3rd April 2018) - Tacea, Filofteia; Loane, Edward; Grixti, Andre; Marsh, Ian B.; Ziahosseini, Kimia
ABSTRACT: Purpose : Rectus muscle resection in thyroid eye disease (TED) is generally avoided due to the risk of worsening restriction or reactivating inflammation. However, for some patients with large-angle strabismus or diplopia in primary gaze despite maximum recession surgery, rectus muscle resection may be beneficial. We report our surgical experience with rectus muscle resection in the management of vertical strabismus associated with TED. Methods : Retrospective review of eight patients with TED and vertical diplopia who underwent vertical rectus muscle resection by a single surgeon (IBM) at a tertiary referral centre in Liverpool, UK, from 2001 to 2013. The goal of surgery was elimination of diplopia in primary and reading position. Vertical deviations were measured in prism dioptres ( ∆ ) before and after surgery at one month, four months and final visit by prism alternate cover testing at ⅓ m and 6 m. Results : The mean ± standard deviation vertical deviation for near and distance reduced significantly from 14.2 ∆ ± 8.4 ∆ and 15.8 ∆ ± 8.8 ∆ pre-operatively to 5.7 ∆ ± 4.9 ∆ and 6.7 ∆ ± 7 ∆ at the four-month visit, respectively ( p < 0.05). At the four-month follow-up, five (62.5%) patients achieved binocular single vision in primary and reading position with either no prisms or prisms less than 5 ∆ . Further recession surgery, Harada-Ito procedure, or lateral rectus resection were necessary in four (50%) patients with persistent diplopia. No patient developed recurrence of inflammation or increased muscle restriction. Conclusions : Vertical rectus resection could be considered as an additional surgical strategy in the management of TED patients with vertical strabismus without adverse sequelae.